Oral Administration of Bisphenol A Directly Exacerbates Allergic Airway Inflammation but Not Allergic Skin Inflammation in Mice. (28th May 2018) - Tajiki-Nishino, Risako; Makino, Emi; Watanabe, Yuko; Tajima, Hitoshi; Ishimota, Makoto; Fukuyama, Tomoki
Abstract: Bisphenol A (BPA) is used in various areas of daily life as a major component of plastic products. However, it is also known as a strong endocrine disruptor that affects the human immune system. Studies have indicated that BPA possibly exacerbates allergic diseases such as atopic dermatitis and asthma. The main aim of this study was to elucidate whether BPA is directly involved in the exacerbation of allergic inflammation. Initially, in vivo experiments with mouse models of allergic inflammation induced by Th2 type hapten toluene-2, 4-diisocyanate (TDI) was performed. Mice were subjected to oral administration of BPA 48, 24, and 4 h before challenge with TDI. Dermal challenge of TDI onto the ear auricle was performed for the allergic dermatitis model, and intratracheal challenge of TDI was performed for the allergic airway inflammation model. In the allergic dermatitis model, ear-swelling response was significantly downregulated by high doses of BPA. The opposite reaction was observed in the allergic airway inflammation model, including significant exacerbation of red coloration in the lung, local cytokine levels, and total IgE levels in serum by BPA administration. To confirm the in vivo results, in vitro experiments with human epidermal keratinocytes (HEKs) and bronchial epithelial (BEAS-2B) cells were carried out. Significant enhancement of cytokine release from BEAS-2B cells but not HEKs in the BPA-treated group supported the in vivo observations. Our results imply that exposure to BPA directly exacerbates allergic airway inflammation but not allergic dermatitis.